Multiple Hazard Uncertainty Visualization Challenges and Paths Forward - Padilla, Lace; Dryhurst, Sarah; Hosseinpour, Helia; Kruczkiewicz, Andrew (Frontiers in Psychology, 2021)
Making decisions with uncertainty is challenging for the general public, policymakers, and even highly trained scientists. Nevertheless, when faced with a need to respond to a potential hazard, people must make high-risk decisions with uncertainty. In some cases, people have to consider multiple hazards with various types of uncertainties. Multiple hazards can be interconnected by location, time, and/or environmental systems, and the hazards may interact, producing complex relationships between their associated uncertainties. The interaction between multiple hazards and their uncertainties can have non-linear effects, where the resultant risk and uncertainty are greater than the sum of the risk and uncertainty associated with individual hazards. Effectively communicating the uncertainties related to such complicated systems should be a high priority as the frequency and variability of multiple hazard events due to climate change continues to increase. However, research on the communication of multiple hazard uncertainties and their interactions remains largely unexplored. The lack of practical guidance on conveying multiple hazard uncertainties is likely due in part to the field's vast expanse, making it challenging to identify entry points. Here we offer a perspective on three critical challenges related to uncertainty communication across various multiple hazard contexts to galvanize the research community. We advocate for systematic considerations of multiple hazard uncertainty communication that focus on trade-offs between complexity and factors, including mental effort, trust, and usability.